CLINICAL, LABORATORY, AND IMMUNOLOGICAL FEATURES OF PATIENTS WITH BRONCHOPULMONARY DISEASES - Kalandarova D.O, (TADQIQOTLAR, 2026)
Introduction Respiratory  system  diseases  continue  to  represent  a  major  challenge  in contemporary medicine due to their high prevalence and significant contribution to morbidity  and  mortality  worldwide,  including  in  Uzbekistan.  Numerous  reports indicate  that  respiratory  diseases  rank  among  the  leading  causes  of  illness,  with incidence rates increasing approximately 2.5 times in recent years [1]. Pneumonia, in particular, remains one of the most life-threatening infectious diseases; in 2019 alone, it  was  responsible  for  nearly  2.5  million  deaths  globally,  including  about  672,000 pediatric cases [2]. Bronchopulmonary disorders—such as chronic bronchitis, chronic obstructive pulmonary disease (COPD), pneumonia, and related conditions—not only impair  patients’  quality  of  life  and  work  capacity  but  also  substantially  increase disability and mortality rates [3].Bronchopulmonary diseases are characterized by both local and systemic inflammatory responses. Alterations in immune system function play a pivotal role in disease development and progression. Previous investigations have  demonstrated  that  patients  with  chronic  bronchopulmonary  pathology  often exhibit  reduced  immunological  reactivity,  manifested  by  decreased  T-lymphocyte counts, disrupted lymphocyte subpopulation balance, diminished natural killer (NK) cell activity, and abnormalities in immunoglobulin levels [4]. These findings suggest the  presence  of  secondary  immunodeficiency,  particularly  in  patients  with  severe disease  courses  [5],  which  in  turn  predisposes  them  to  recurrent  infections  and dysregulated inflammatory responses. Study objective: To evaluate clinical manifestations, laboratory parameters, and immunological alterations in patients with bronchopulmonary diseases according to disease  severity,  and  to  perform  statistical  analysis  in  order  to  formulate evidence-based conclusions and clinical recommendations.